Project management education in Croatia : a focus on the IT sector needs - Bestvina Bukvić, Ivana (Array, 2020)
Since today's dynamic and competitive business environment increasingly requires additional level of competence, the project manager is, certainly, a profession whose value and demand is growing. As to reach the project objective, the project manager should have an adequate education, which is the reason why the corporations, especially in the Information Technology (IT) industry, are among leaders in investment to project management education and certification. The aim of this paper is to contribute to the identification and understanding of the project management education model in Croatia and explore possibilities for its improvements, especially in the field of the project management in the IT industry. For that reason, through 2018 and 2019, authors conducted the research on availability of project management education programs in Croatia, opportunities for international certification as well as attitudes of the project management professionals in IT sector on the existing education model. The study suggests that there is a growing trend of project managers’ certification, especially in the IT industry, as well as a variety of informal programs for project management education. Simultaneously, there is a lack of project management university study programs. Empirical results show that project management study programs lack the practical segment and are, in most cases, offering only fundamental theoretical knowledge. Therefore, authors, on the basis of the literature review and analysis of IT sector needs assessment, provide recommendations of the domains, to be included into future university study programs.